ADOLESCENT BARRIERS IN ACCESSING REPRODUCTIVE HEALTH SERVICE IN DEVELOPING COUNTRIES - Utami, Siswi; Hayati, Elli Nur; Rosyida, Luluk (LPPM Universitas Prima Nusantara Bukittinggi, 2020)
Background: Teenagers are those aged 10-19 years who are future leaders and are a human resource who does not receive enough attention. One-fifth of the world's population is a teenager who mostly lives in developing countries. Society considers adolescents to be healthier, but adolescents are more vulnerable and at higher risk of contracting diseases that cause death. In 2015 1.3 million people died in the world during adolescence which could have been prevented. This occurs in low- and middle-income countries (LMICs), which make up two-thirds of Africa's 45 per cent. About 16 million adolescent girls aged 15-19 years and around 2.5 million girls under 16 give birth each year in developing countries. There are about 3 million young women who have unsafe abortions every year aged 15-19 years. Globally, about 2 million adolescents are infected with the human immune virus (HIV), and more than 41 per cent of adolescents become infected with new HIV each year.Purpose: to assess barriers for adolescents to access reproductive health services in developing countries.Method: Appraisal studies program using Critical Appraisal Skills Program (CASP) data sources obtained from PubMed with 2009 – 2019.Results: inadequate space, no privacy, limited service hours, poor service attitude, lack of information, a distance of clinics, high transportation costs, clinics aimed at married couples. Lack of human resources, parental support, peer influence, religion and weak community traditions for adolescent health interventions also trigger adolescents not to access reproductive health clinics.Conclusion: The obstacles for adolescents in accessing reproductive health services are the level of infrastructure, the individual level, the level of human resources and the community level